2004
DOI: 10.1081/ja-120028488
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of Noninjection Drug-Use Implements as a Risk Factor for Hepatitis C

Abstract: This study examined sharing noninjection drug implements as a risk factor for hepatitis C (HCV) infection among women drug users (n = 123) with no history of drug injection. Participants were street-recruited from East Harlem, New York City, between October 1997 and June 1999. Participants were administered a survey measuring risk factors for HCV. Prevalence of HCV and HIV infections was 19.5% and 14.6%, respectively. Multiple logistic regression determined significant associations between sharing noninjection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 14 publications
4
87
1
4
Order By: Relevance
“…We found 28 published reports that met our criteria (Allwright et al, 2000;Baozhang et al, 1997;Broers et al, 1998;Chang et al, 1999;Denis et al, 2000;Feldman et al, 2000;Fuller et al, 2004;Galperim et al, 2004;Garten et al, 2004;Gyarmathy et al, 2002;Harsch et al, 2000;Hershow et al, 1998;Howe et al, 2005;Koblin et al, 2003;Lai et al, 2001;Maayan et al, 1994;Mathei et al, 2005;Njoh et al, 1997;Nyamathi et al, 2002;Quaglio et al 2003a;Quaglio et al 2003b;Santana Rodriguez et al, 1998;Shrestha et al, 1998;Strasfeld et al, 2003;Tortu et al, 2001;Tortu et al, 2004;Van Ameijden et al, 1993;Ward et al, 2000). One report included two separate studies, both of which were included (Tortu et al, 2001) and which appear in Table 1 in two separate rows; two reports were by the same author and indicated the same overall seroprevalence and sample size, therefore we counted this as one study (Quaglio et al 2003a(Quaglio et al & 2003b.…”
Section: Study Characteristicsmentioning
confidence: 85%
See 3 more Smart Citations
“…We found 28 published reports that met our criteria (Allwright et al, 2000;Baozhang et al, 1997;Broers et al, 1998;Chang et al, 1999;Denis et al, 2000;Feldman et al, 2000;Fuller et al, 2004;Galperim et al, 2004;Garten et al, 2004;Gyarmathy et al, 2002;Harsch et al, 2000;Hershow et al, 1998;Howe et al, 2005;Koblin et al, 2003;Lai et al, 2001;Maayan et al, 1994;Mathei et al, 2005;Njoh et al, 1997;Nyamathi et al, 2002;Quaglio et al 2003a;Quaglio et al 2003b;Santana Rodriguez et al, 1998;Shrestha et al, 1998;Strasfeld et al, 2003;Tortu et al, 2001;Tortu et al, 2004;Van Ameijden et al, 1993;Ward et al, 2000). One report included two separate studies, both of which were included (Tortu et al, 2001) and which appear in Table 1 in two separate rows; two reports were by the same author and indicated the same overall seroprevalence and sample size, therefore we counted this as one study (Quaglio et al 2003a(Quaglio et al & 2003b.…”
Section: Study Characteristicsmentioning
confidence: 85%
“…Those that did give characteristics reported that their samples were predominantly male (62 percent-100 percent male), although there were five studies that either recruited only females or restricted their analysis to female subjects (Feldman et al, 2000;Hershow et al, 1998;Tortu et al, 2004;Tortu et al, 2001;Ward et al, 2000). The NIDUs in the majority of the reports we located were relatively young; among those studies that reported age information, the mean age of the subjects varied between 25 and 30 years old.…”
Section: Sample Characteristicsmentioning
confidence: 91%
See 2 more Smart Citations
“…vated risk factors in this group (e.g., marginalization, sex work, unsafe injection practices, etc) (Roy et al, 2001;Weinstock, Bolan, Reingold, & Polish, 1993;Thorpe, Ouellet, Levy, Williams, & Monterroso, 2000;Tortu, McMahon, Pouget, & Hamid, 2004). Among users in Canadian cities, crack use with unsafe materials and paraphernalia sharing is common (Haydon et al, 2005a).…”
Section: T H E M E N S C H W E R P U N K Tmentioning
confidence: 99%